Description of embryonic development and ultrastructure in miracidia of Cardiocephaloides longicollis (Digenea, Strigeidae) in relation to active host finding strategy in a marine environment - Born-Torrijos, Ana; Holzer, Astrid S; Raga, Juan A; van Beest, Gabrielle S; Yoneva, Aneta (Journal of morphology, 2017)
The functional ultrastructure and embryonic development of miracidia in naturally released eggs of the trematode Cardiocephaloides longicollis were studied using light and transmission electron microscopy. This species has operculated eggs and embryogenesis occurs in the marine environment before an actively infecting ciliated miracidium hatches. Six different developmental stages were identified. The lack of pores in the eggshell indicates its impermeability and the miracidium's dependency on glycogen nutritive reserves, contained in numerous vitellocytes in early embryos. As the development advances, these merge into larger vitelline vacuoles that encircle the miracidium and may aid its hatching. Tissue and primary organ differentiation were observed in advanced stages, i.e., terebratorium, glands, cerebral ganglion, peripheral sensory endings, and eyespots. The anterior part of the body contains a single apical and paired lateral glands, as well as two types of sensory endings, which permit location, adhesion, and penetration of the host. No previous studies describe the embryonic development and ultrastructure of miracidia in strigeids, however, some of the structural features shared with other, well described species with unknown life cycles are emphasised. This study highlights that ultrastructural data have to be interpreted in relation to parasite biology to understand the structural requirements of specific parasite strategies.
Keywords: parasite strategies; Animals; ovum; ekosystém; Egg Shell; Trematoda; vaječná skořápka; Ecosystem; TEM; Ovum; zvířata; embryonální vývoj; functional; trematode egg; embryogenesis; Embryonic Development; developmental stages